2008
DOI: 10.1177/000313480807401209
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis Suppurativa Complicated by Squamous Cell Carcinoma

Abstract: Hidradenitis suppurativa (HS) is a chronic inflammatory condition affecting the apocrine glands of the axilla, groin, and perianal region. Although it is a common condition, it is rarely associated with squamous cell carcinoma (SCC). There have been only 41 reports of this uncommon complication of HS in the literature. This study includes two uncommon presentations of HS associated with SCC along with a literature review. The first patient developed diffuse abdominal carcinomatosis from SCC in the anogenital r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…The incidence of MU arising from long-standing HS varies from 1% to 3.2%. [ 5 ] Transformation from HS to SCC may be explained by chronic irritation and infection, which lead to proliferative epidermal changes and increased rate of spontaneous mutations. By far, HS complicating SCC was rarely reported despite a low occurrence rate of HS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of MU arising from long-standing HS varies from 1% to 3.2%. [ 5 ] Transformation from HS to SCC may be explained by chronic irritation and infection, which lead to proliferative epidermal changes and increased rate of spontaneous mutations. By far, HS complicating SCC was rarely reported despite a low occurrence rate of HS.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation may be that male tends to have a high morbidity in anogenital or perineal region while female in axillary. [ 8 ] Concomitant diseases accompanied with these cases included hypercalcemia, [ 5 , 9 ] follicular occlusion triad, [ 10 ] Crohn disease, [ 11 ] osteomyelitis, [ 12 ] spina bifida, [ 13 ] polyneuropathy, [ 14 ] etc.…”
Section: Discussionmentioning
confidence: 99%
“…While cases reporting detailed histology ( N = 58) were most often WD (53·4%; Table ), SCC in HS can be aggressive, with local invasion and increased risk of metastasis and mortality . Constantinou et al reviewed 43 patients with HS complicated by SCC and demonstrated 48% local or distant recurrence, even among patients who had ‘curative’ surgery with negative margins, with mortality approaching 50% . Lavogiez et al found that nearly half of 38 patients with SCC in HS had lymph node metastases on follow‐up, versus 5–10% in SCC of any aetiology, and that 57% of 52 patients with follow‐up expired within 2 years, with only 19% alive and free of recurrence after 1 year .…”
Section: Discussionmentioning
confidence: 99%
“…Hidradenitis suppurativa (HS) is a chronic, recurrent inflammatory disorder of the hair follicles in anatomic areas rich with apocrine glands. Patients develop long‐standing painful subcutaneous nodules, sinus tracts and scarring, mainly in the axillae, groin and buttocks . As with other chronic inflammatory disorders, squamous cell carcinoma (SCC) may arise in the setting of chronic inflamed lesions of HS.…”
Section: Introductionmentioning
confidence: 99%
“…Well known risk factors for development of CSCC include UV exposure, immunosuppression, exposure to ionizing radiation or chemical carcinogens, human papillomavirus infection. [ 6 ] Other conditions reported to have been associated with cutaneous SCC include acne conglobata, hidraadenitis suppurativa,[ 7 ] dissecting folliculitis of the scalp, lupus vulgaris,[ 8 ] chronic deep fungal infection, xeroderma pigmentosum,[ 9 ] dystrophic epidermolysis bullosa,[ 10 ] epidermodysplasia verruciformis, dyskeratosis congenita, porokeratosis of Mibelli,[ 11 ] Marjolin's ulcer, burn or thermal injury,[ 12 ] venous ulcers, lymphedemas, discoid lupus erythematosus,[ 13 ] erosive oral lichen planus, lichen sclerosis et atrophicus, mutilating keratoderma, and necrobiotic lipoidica.…”
Section: Discussionmentioning
confidence: 99%